Analisa Kesalahan Penulisan Huruf Hamzah (Washl / Qath’i) Pada Siswa/i Kelas XII Madrasah Aliyah Negeri 1 Medan - Ramadani, Jesi; Anwar, Mutia Rakhma; Nasution, Nilma Wahyuni; Nasution, Sahkholid (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research was motivated by the discovery of students who had low ability in writing Arabic, especially in the hamzah letters. Therefore, an analysis was carried out to describe the forms of student errors in writing the hamzah letters in Arabic texts. The aim of the research is descriptive using a qualitative approach and using theoryWriting skills (maharah Al kitabah/writing ability) is the ability to describe or express the contents of one's thoughts, from the simple aspects of writing words to the complex aspects of composing music, and using quantitative methods on Arabic writing assignment sheets on documents related to writing hamzah letters for analysis of class XII students of Madrasah Aliyah Negeri 1 Medan. Data was collected using documentation, observation and interview methods. Research result The results of the research show that the remaining and female students at Madrasah Aliyah Negeri 1 Medan in class understand and cannot fully differentiate between the letters Hamzah and Alif.